Pelaksanaan Peraturan Daerah Kabupaten Banyumas Nomor 9Tahun 2009 Tentang Kedudukan Keuangan Kepala Desa danPerangkat Desa - Ninik Hartariningsih; Esti Ningrum (Wijayakusuma Law Review, 2021)
The purpose of this study was to determine how the implementation of the Regional Regulation No. 9 of 2009 andhow the results achieved with the implementation of this Regulation. While the usefulness of this research study isTeoritis.hasil expected to be contributions to the development of the science of law and various legal productsproduced by the Regional Government of Banyumas, whereas Practical Uses the results of this study are expectedto assist local governments in finding out if there is a constraint jalan field. Besides, it is also the implementation ofthe regulation can achieve prosperity for the village head and the device village.Adapun This research usednormative juridical approach, which is based approach Normative legal disciplines, as sisitem rules and the dataor examine the problems adhering to the terms of Juridical . Specifications Research, Research this Normative legaluse, the type of Clinical Legal Research, the research to find the case law In Abstrakto In Conereto. The material ofthis study is the Implementation of Regulation No. 9 of 2009. The location Research, Some Banyumas RegencyVillage and University library Wijayakusuma Purwokerto, Banyumas Regional Library. Sekender Data SourceData is sourced in legislation, official documents that exist at the district and village, literature and journals andthe internet was associated with law.